Gestión administrativa y su incidencia en la rentabilidad de la cooperativa de Taxis Rey en el cantón Quevedo, año 2023 - Pérez Kutaytón, Janeth Cristina (2025)
This research was conducted in the Quevedo canton in 2024. Its objective was to analyze administrative management and its impact on the profitability of the Rey Taxi Cooperative. The methodology used was analytical, descriptive, qualitative, quantitative, random, and non-experimental. Data was obtained through surveys of the cooperative's management and service users. The results showed that the cooperative's organizational structure is clear and efficient. Cooperative communication system is effective. Frequent financial analysis is not conducted, but basic profitability indicators are used to measure the cooperative's financial situation.